Antimicrobial and Immunomodulatory Effects of Selected Chemokine and Antimicrobial Peptide on Cytokine Profile during Salmonella Typhimurium Infection in Mouse - Astrid Tuxpan-Pérez; Marco Antonio Ibarra-Valencia; Blanca Elisa Estrada; Herlinda Clement; Ligia Luz Corrales-García; Gerardo Pavel Espino-Solis; Gerardo Corzo (MDPI AG, 2022)
The antimicrobial and immunomodulatory capacities of the peptide Css54 and the chemokine MCP-1 were tested. The first, a peptide isolated from the venom of the scorpion Centruroides suffusus suffusus was synthesized chemically. In contrast, the second is a monocyte chemoattractant expressed as a recombinant protein in our lab. It was observed in vitro that Css54 inhibited the growth of Salmonella enterica serovar Typhimurium (6.2 µg/mL). At high concentrations, it was toxic to macrophages (25 µg/mL), activated macrophage phagocytosis (1.5 µg/mL), and bound Salmonella LPS (3 µg/mL). On the other hand, the recombinant MCP-1 neither inhibited the growth of Salmonella Typhimurium nor was it toxic to macrophages (up to 25 µg/mL), nor activated macrophage phagocytosis or bound Salmonella LPS (up to 3 µg/mL). Although it was observed in vivo in mice Balb/C that both Css54 and MCP-1 did not resolve the intraperitoneal infection by S. Typhimurium, Css54 decreased the expression of IL-6 and increased IL-10, IL-12p70, and TNF-α levels; meanwhile, MCP-1 decreased the expression of IFN-γ and increased IL-12p70 and TNF-α. It was also observed that the combination of both molecules Css54 and MCP-1 increased the expression of IL-10 and TNF-α.